2012
DOI: 10.4236/oja.2012.23011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging of Spinal Vertebrae to Study Scoliosis

Abstract: Scoliosis is a musculoskeletal disorder manifested as a three-dimensional spinal deformity. It affects 2% -3% of the adolescent population. The conventional method to diagnose scoliosis is to measure the Cobb angle from posteroanterior radiograph. Since radiation exposure is not desirable for patients, other non-ionizing methods have been explored. Among all the non-ionization methods, ultrasound (US) is a potential cost-effective method. However, our understanding of US interaction with the vertebrae or the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…As shown in Fig. 2a, the laminae, which were strong reflection points (around the two lowest points of the ''W-shape'') due to a strong reflection signal from the lamina area [17], were used to assess the AVR. A line was drawn through the centers of the left and right laminae and the angle formed between this line and the reference horizontal level indicated the AVR angle.…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 2a, the laminae, which were strong reflection points (around the two lowest points of the ''W-shape'') due to a strong reflection signal from the lamina area [17], were used to assess the AVR. A line was drawn through the centers of the left and right laminae and the angle formed between this line and the reference horizontal level indicated the AVR angle.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…However, both teams acquired data while subjects were in the prone position, which affected the spinal deformity assessment. Recently, Chen et al [16,17] validated that upright ultrasound spine images could be obtained and the center of lamina (COL) method using the ultrasound images provided both Cobb angle and AVR measurements. The Cobb angle validation studies were reported [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The recorded echoes are stored, 183 delayed, and then summed to produce an ultrasound signal. The 184 scanner was previously used to study scoliosis [22]. 185 The two array probes used are the 16-element (2.25L16) and 186 64-element (2.25L64) array probes with a central frequency of 187 2.25 MHz (Fig.…”
mentioning
confidence: 99%
“…To measure the coronal curvature on the ultrasound image, the centers of laminae (COL) method introduced by Chen et al [19,20] was applied. The centers of laminae at the end vertebra levels were manually selected on the coronal plane of the ultrasound image.…”
Section: Methodsmentioning
confidence: 99%